2012
DOI: 10.1071/an11099
|View full text |Cite
|
Sign up to set email alerts
|

Chicks and single-nucleotide polymorphisms: an entrée into identifying genes conferring disease resistance in chicken

Abstract: Abstract. Marek's disease (MD) is one of the most serious chronic infectious disease threats to the poultry industry worldwide. Selecting for increased genetic resistance to MD is a control strategy that can augment current vaccinal control measures. Although our previous efforts integrating various genomic screens successfully identified three resistance genes, the main limitation was mapping precision, which hindered our ability to identify and further evaluate highconfidence candidate genes. Towards identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 30 publications
(29 reference statements)
0
1
0
Order By: Relevance
“…With modern statistical and genomic tools, Li et al [ 8 ] reported two loci associated with MD resistance through genome-wide association study (GWAS). However, the resolution limits of these strategies make it difficult to identify the underlying causative genes, and the variants only explain a small proportion of total genetic variation [ 9 ], leaving a large part of variation unexplained [ 10 ]. More recently, Cheng et al [ 11 ] found that SNPs in allele-specific expression (ASE) genes captures more than 83 % of the additive genetic variation of MD resistance, demonstrating that the most of the ASE genes are strong candidates of underlying genes of MD resistance.…”
Section: Introductionmentioning
confidence: 99%
“…With modern statistical and genomic tools, Li et al [ 8 ] reported two loci associated with MD resistance through genome-wide association study (GWAS). However, the resolution limits of these strategies make it difficult to identify the underlying causative genes, and the variants only explain a small proportion of total genetic variation [ 9 ], leaving a large part of variation unexplained [ 10 ]. More recently, Cheng et al [ 11 ] found that SNPs in allele-specific expression (ASE) genes captures more than 83 % of the additive genetic variation of MD resistance, demonstrating that the most of the ASE genes are strong candidates of underlying genes of MD resistance.…”
Section: Introductionmentioning
confidence: 99%